Molecular Understanding of the Role of Catalyst Particle Arrangement in Local Mass Transport Resistance for Fuel Cells - Aoxin Ran; Linhao Fan; Chasen Tongsh; Jiaqi Wang; Zhengguo Qin; Qing Du; Meng Ni; Kui Jiao (Advanced Science)
Abstract Platinum (Pt) catalyst performance loss caused by a high local oxygen transport resistance is an urgent problem to be solved for proton exchange membrane fuel cells (PEMFCs). Rationally arranging Pt particles on carbon support is the primary approach for reducing mass transport resistance. Herein, using a unique method coupling Hybrid Reverse Monte Carlo, molecular dynamics simulations, and experimental measurements, a Pt particle arrangement strategy is proposed to reduce local oxygen transport resistance, based on a molecular‐level understanding of its impact. The densely arranged Pt particles with a small interparticle distance lead to the denser ionomer layer due to the co‐attraction effect, leading to a high local oxygen transport resistance. The nonuniformly arranged Pt particles with various interparticle distances cause the heterogeneous ionomer density, inducing the heterogeneous oxygen transport. Increasing the Pt‐Pt interparticle distance from 2 to 5 nm substantially reduces the local oxygen transport resistance by over 50%. The uniform arrangement of Pt particles makes the ionomer layer density more homogeneous, resulting in more uniform oxygen transport. Therefore, uniformly arranging Pt particles with an interparticle distance of >5 nm on carbon support is preferred for reducing local oxygen transport resistance and improving the homogeneity of oxygen transport.